Estradiol-Mediated Axogenesis of Hypothalamic Neurons Requires ERK1/2 and Ryanodine Receptors-Dependent Intracellular Ca2+ Rise in Male Rats - Cabrera Zapata, Lucas E.; Bollo, Mariana; Cambiasso, María Julia (Frontiers in Cellular Neuroscience, 2019)
17β-estradiol (E2) induces axonal growth through ERK1/2-MAPK cascade in hypothalamic neurons of male rat embryos in vitro, but the mechanism that initiates these events is poorly understood. This study reports the intracellular Ca2+ increase that participates in the activation of ERK1/2 and axogenesis induced by E2. Hypothalamic neuron cultures were established from 16 day-old male rat embryos and fed with astroglia-conditioned media for 48 h. E2-induced ERK phosphorylation was completely abolished by a ryanodine receptor (RyR) inhibitor (ryanodine) and partially attenuated by an L-type voltage-gated Ca2+ channel (L-VGCC) blocker (nifedipine), an inositol-1,4,5-trisphosphate receptor (IP3R) inhibitor (2-APB), and a phospholipase C (PLC) inhibitor (U-73122). We also conducted Ca2+ imaging recording using primary cultured neurons. The results show that E2 rapidly induces an increase in cytosolic Ca2+, which often occurs in repetitive Ca2+ oscillations. This response was not observed in the absence of extracellular Ca2+ or with inhibitory ryanodine and was markedly reduced by nifedipine. E2-induced axonal growth was completely inhibited by ryanodine. In summary, the results suggest that Ca2+ mobilization from extracellular space as well as from the endoplasmic reticulum is necessary for E2-induced ERK1/2 activation and axogenesis. Understanding the mechanisms of brain estrogenic actions might contribute to develop novel estrogen-based therapies for neurodegenerative diseases.